2022
DOI: 10.1177/10870547221099963
|View full text |Cite
|
Sign up to set email alerts
|

Is Processing Speed (Gs) related to Hyperactivity (As a Narrow Cognitive Area of Gps): A Dimensional Approach to Heterogeneity of Clinical and WISC-IV Cognitive Profiles in ADHD From RDoC/HiTOP Perspective

Abstract: Objective: The aim of this study was to investigate the relationship between symptomatology and the Wechsler Intelligence Scale for Children, Fourth Edition (WISC-IV) cognitive profiles in Attention Deficit and Hyperactivity Disorder (ADHD), taking into account clinical heterogeneity. Method: The WISC-IV was administered to 60 children aged 6 to 13 years with ADHD who had not previously taken psychotropic medication. Conners Teacher-Rating Scale (CTRS-R/L) and Conners Parent-Rating Scale (CPRS-R/L) were comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…Therefore, the attention deficit might produce various degree of impact on to the cognitive performance. 35,53 Interestingly, we found that the PRI scores of children with ADHD were better than the Chinese norm, which was consistent with the study of Walg et al, in contrary to the study of Dinçer et al Notably, our study and the study of Walg et al were based on boys and girls, and the study of Dinçer et al was only based on boys, suggesting the impact of gender difference onto the cognition. As opposed to VCI which measures crystallized intelligence, PRI measures the fluid.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, the attention deficit might produce various degree of impact on to the cognitive performance. 35,53 Interestingly, we found that the PRI scores of children with ADHD were better than the Chinese norm, which was consistent with the study of Walg et al, in contrary to the study of Dinçer et al Notably, our study and the study of Walg et al were based on boys and girls, and the study of Dinçer et al was only based on boys, suggesting the impact of gender difference onto the cognition. As opposed to VCI which measures crystallized intelligence, PRI measures the fluid.…”
Section: Discussionsupporting
confidence: 89%
“…The continuous variables were presented as mean ± standard deviation (SD), and categorical variables were presented as percentages. 35 One-sample Wilcoxon signed rank test was used to compare the WISC-IV scores of ADHD children in our study with the reliability norms of Chinese children, and dependent sample t -test was used to compare differences in the WISC-IV index scores of our samples. In addition, Mann–Whitney U test was used to assess the difference in the WISC-IV scores between the ADHD groups with and without comorbid symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation